THE FEATURES OF ASSESSMENT OF LIGHTING SYSTEMS OF TRANSPORT MACHINES - Шаша, Ігор Костянтинович; Маренко, Геннадій Миколайович; Кайдалов, Руслан Олегович (Eastern-European Journal of Enterprise Technologies, 2010)
The features of method of model experiments of estimation of work of the light systems of transport machines are considered in the article. The specific of perception of high-quality and quantitative information a driver oh external environments was determined.